2015
DOI: 10.1515/amma-2015-0059
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Rubber Dam Usage Among Dental Practitioners and Final Year Students in Tirgu Mures: A Questionnaire Survey

Abstract: The purpose of this study was to determine the prevalence of rubber dam usage among endodontists, other specialized practitioners, general practitioners and undergraduate final year students in Tirgu-Mures, Romania. Material and method: A questionnaire was distributed among 250 subjects. Final year students and dentists were surveyed in relation to their prevalence of rubber dam usage. Results: Overall response rate was 72,4. While 84,07% of the subjects knew about the advantages, only 49,72% used it during th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 12 publications
1
0
1
Order By: Relevance
“…According to the 2020 AAPD guidelines [ 35 ], rubber dam isolation is the gold standard for pulpal treatments. Nonetheless, many studies have reported, in accordance with our findings, that rubber dams are highly preferable in pediatric patients [ 27 , 36 , 37 ].…”
Section: Discussionsupporting
confidence: 92%
“…According to the 2020 AAPD guidelines [ 35 ], rubber dam isolation is the gold standard for pulpal treatments. Nonetheless, many studies have reported, in accordance with our findings, that rubber dams are highly preferable in pediatric patients [ 27 , 36 , 37 ].…”
Section: Discussionsupporting
confidence: 92%
“…The present study showed that only about 10% of general dentists performed rubber dam isolation, while studies have shown that this number is more than 50% in the United States and Europe [15,16]. A lower rate was reported in East Asia [17].…”
Section: Discussioncontrasting
confidence: 50%